Numerical and experimental analysis of a hybrid wind-wave offshore floating platform’s hull - Hallak, Thiago S. (2018)
This paper presents a study regarding a novel hybrid concept for both wind and wave energy offshore. The concept resembles a semi-submersible wind platform with a larger number of columns. Wave Energy Devices such as point absorbers are to be displayed around the unit, capturing wave energy while heaving and also enhancing the stability of the platform. In this paper, a first numerical study of the platform’s hull, without Wave Energy Converters, is carried out. Experiments in wave basin regarding the same unit have been conducted and the results are presented and compared to the numerical ones. Both stability and seakeeping performances are assessed and compared.